(untitled) (Journal on studies and research of academic knowledge, 2024)
There are several business models that incorporate innovation, including the strategic management model based on risk management, open innovation, but it should be noted that more than 90% of all innovations in business models are recombinations of ideas, concepts, and previously existing models. The role played by technological innovation in solving some societal problems such as air and water pollution is fundamental. The objective of this work is to propose an innovation model for sustainable management in a crisis context for supermarkets and convenience stores through the analysis of the cases that are considered to have responded effectively to the crisis context unleashed by the health emergency established by the distancing protocol as a preventive measure against the spread of COVID 19, the cases were Biggie and Casa Grutter. The methodological design covers the documentary and field bibliographic modality, with exploratory, descriptive, explanatory levels using analytical, synthetic and inductive methods. The result provides significant contributions from the perception of customers and purchasing criteria as well as from managers and management in the context of a health emergency. It is concluded that a purchasing model through virtual platforms is an effective model, that it has a market potential and that the management must be sustainable, that is, take into account the triple impact transversally to the entire organization according to the statement of the customers.